Identification of the Population Structure of Myzus persicae (Hemiptera: Aphididae) on Peach Trees in China Using Microsatellites. Issue 1 (22nd June 2015) - Li, Jie; Cao, Jinjun; Niu, Jianqun; Liu, Xiaoxia; Zhang, Qingwen
Abstract : In this study, we characterized the genetic structure of Myzus persicae (Sulzer) (Hemiptera: Aphididae) populations in China using microsatellites. We expected that these data will reveal the genetic relationships among various populations of M. persicae and will be of value in the development of better methods for pest control. Four hundred sixty individuals from 23 areas over 13 provinces were collected in the early spring of 2010, all from their primary host, Prunus persicae . The markers analyzed were highly polymorphic, as demonstrated by the expected heterozygosity value ( H e = 0.861) and the Polymorphism Information Content (PIC = 0.847), which indicated that M. persicae maintains a high level of genetic diversity. Analysis of molecular variance revealed an intermediate level of population differentiation among M. persicae populations ( F ST = 0.1215). Geographic isolation existed among these populations, and, consequently, the genetic structure of the populations was split into a southern group and a northern group divided by the Yangtse River.